Intention and Attention within Sheldrake’s Morphic Resonance Fields in Nature and Humans: Network Interaction in Weather. Eyes Closed Images during Research and non Research: Similar Artistic and Scientific Images - Shinnick, Phillip; Porter, Lawrence; Maize, Joseph (Cosmos and History: The Journal of Natural and Social Philosophy, 2018)
Mathematics, proper language, instrument measurement, logic, skepticism, materialism, reductionism and an assessment of other scientific works as been the way since the French Revolution. Field theory in physics opens an opportunity to go back to natural philosophy and empirical observation swallowed by current events in science. Sheldrake’s morphogenetic resonance from evolutionary biology fits field theory’s necessary subject/object singularity and a bridge between genes and evolution. Empirical observation for science means eyes open. Over thirty years eyes closed research observation gives images which are more stable during research periods and do not repeat themselves during non research periods. However, some non-repeating individual images show up in art during the last five hundred years confirming human morphogenetic resonance "image habits" in humans over time. Instrument images show similarities to non-repeating human images; Born’s images of an atom, a galaxies from a space telescope, gold ions colliding, six iterations of a set of states [x,y] passed through the logistic map and an oscilloscope image reading of a tornado. Changing weather patterns by Qigong and assessing organ fields in the body shows human influences to nature and the self through lines of essence. A patient with a serious painful spinal injury created a line of essence with animal spirit for healing. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>